(untitled) - Dhlamini, Z. (Rome, 2005)
Scarcity of information on biotechnology activities in developing countries has prompted FAO to build up an inventory of biotechnology products and techniques in use or in the pipeline in these countries. The inventory has been compiled and organized into a searchable online database entitled FAO-BioDeC (FAO Biotechnology in Developing Countries). This document presents a preliminary assessment and analysis of the status of development, adoption and application of crop biotechnologies in developing and transition countries based on a review of the information in the FAO-BioDeC database as of August 31, 2004.
Keywords: Plant biotechnology,Công nghệ sinh học cây trồng; Developing countries,Phát triển đất nước